Macroecological patterns of fruit infestation rates by the invasive fly Drosophila suzukii in the wild reservoir host plant Sambucus nigra. (26th June 2022) - Ulmer, Romain; Couty, Aude; Eslin, Patrice; Catterou, Manuella; Baliteau, Lucas; Bonis, Anne; Borowiec, Nicolas; Colinet, Hervé; Delbac, Lionel; Dubois, Françoise; Estoup, Arnaud; Froissard, Joris; et al.
Abstract: The invasive pest Drosophila suzukii is a fruit fly native to Asia that infests a wide variety of fruits. Wild plant species are major reservoirs for D . suzukii populations but their infestation rates vary greatly among geographical areas. We aimed at disentangling the relative roles of macroclimatic, landscape and local factors in the rate of D . suzukii infestation of elderberry fruits ( Sambucus nigra ), a major wild host plant in Europe. We collected elderberry fruits across 215 sites distributed in 13 regions from North to South of France. We counted the number of emerging D . suzukii adults and tested for the effect of macroclimatic, landscape, local biotic and abiotic variables, as well as plant traits using linear mixed models. Site latitude and mean daily maximum temperature since the beginning of the year had respectively the strongest positive and negative effects on mean infestation rates across regions. Infestation rates also increased with forest cover in a 100 m radius around sampling sites. This study shows the importance of taking into account multiple scales and factors, from the fruit characteristics (i.e. maturity) to landscape composition and macroclimatic variables, when studying the interaction between D . suzukii and its host plants. Abstract : Impacts of environmental factors on Drosophila suzukii‐Sambucus nigra relationships at different scales.